A review of developments in the family of modular multilevel cascade converters. Issue 9 (19th June 2018) - Akagi, Hirofumi
Abstract : This paper starts with a historical review of the family of modular multilevel cascade converters, and the topology and terminology of the family. Then, it answers the following question: 'What motivated the author to apply phase‐shifted‐carrier pulse‐width modulation (PSC PWM) to the family?' The success in academic research on this application owes to integrating inter‐cluster balancing or inter‐arm balancing control into the middle layer of a hierarchical control system consisting of three layers. This integration makes it easy to expand the PSC PWM to any bridge‐cell or chopper‐cell count per cluster or arm. Finally, this paper ends with future scenarios of a few promising family members and their practical applications, from the personal experience and view of the author. © 2018 Institute of Electrical Engineers of Japan. Published by John Wiley & Sons, Inc.